Potential and impact study of amman high frequency speed bus, a case study - Ashraf Samarah; Afaq Hiary; Ameera Amayira; Hiba Asheesh; Ayman Y. Al-Rawashdeh (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The current study proposes the utilization of solar panels to power high frequency speed buses like the Bus Rapid Transit in Am-man city.  Based on Photo Voltaic technology, mounting PV solar panels system on the top of the track of the high frequency bus, ar-ranged at azimuth angle ranging between 0°- 90° with the best tilt angle measured 12°, along an actual unshaded track of 18 km (of the 25 km total pathway track), resulted in the generation of more than18 MWp (On Grid system). Such power is used not only to charge the bus and to operating facilities inside the city instead of the conven-tional ways as illustrated in the coming later.